2018
DOI: 10.1088/1361-665x/aae00e
|View full text |Cite
|
Sign up to set email alerts
|

A novel rotary magnetorheological flexible joint with variable stiffness and damping

Abstract: To transfer torque while reducing vibration and shock, a rotary magnetorheological flexible joint (MRFJ) with tunable stiffness and damping characteristics is proposed in this study. Equivalent variable stiffness and damping principle for the MRFJ is derived analytically. The structure and parameters of the MRFJ are designed. The variable stiffness and damping characteristics of a prototype of MRFJ is measured. The test results show that the variable stiffness and damping characteristics of the MRF can be tune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…As a new type of mechanical device, MRF dampers and mounts have the ability to provide variable damping (Xu et al, 2018b), mitigate adverse vibration (Dong et al, 2018), and recycle kinetic energy (Wang et al, 2018), and play a key role in many fields (Ha et al, 2018;Lv et al, 2020). For different engineering applications, the development of high-performance MRF dampers and mounts has always been a research hotspot, such as adjusting local structure size, optimizing internal magnetic field, and updating configuration design.…”
Section: Magnetorheological Fluid Dampers and Mounts In Engineering Amentioning
confidence: 99%
“…As a new type of mechanical device, MRF dampers and mounts have the ability to provide variable damping (Xu et al, 2018b), mitigate adverse vibration (Dong et al, 2018), and recycle kinetic energy (Wang et al, 2018), and play a key role in many fields (Ha et al, 2018;Lv et al, 2020). For different engineering applications, the development of high-performance MRF dampers and mounts has always been a research hotspot, such as adjusting local structure size, optimizing internal magnetic field, and updating configuration design.…”
Section: Magnetorheological Fluid Dampers and Mounts In Engineering Amentioning
confidence: 99%
“…Greiner-Petter et al [25] used one magneto-rheological fluid damper with two passages and two parallel springs to provide four different levels of system stiffness. Similar variable stiffness devices with magnetorheological fluid dampers and two springs were also documented in [26][27][28]. Apart from the switching between the connection and disconnection of one spring to or from system components, varying the number of active spring coils directly to achieve stiffness variation has also been documented [29,30].…”
Section: Introductionmentioning
confidence: 76%
“…The experimental results show that the robot leg have good adaptability when walking on relatively hard terrain, are easy to control, and have a simple structure. Dong et al [22] designed a rotary MR flexible joint with adjustable stiffness and damping to reduce the vibration caused by torque transmission. Through theoretical analysis and experimental verification of the mechanical properties of the joint, it has been shown that the stiffness and damping performance of the joint can be independently controlled, its equivalent stiffness and the damping coefficient can be adjusted between 5.15-12.28 Nm rad −1 and 0.83-3.6 kNs m −1 , respectively.…”
Section: Introductionmentioning
confidence: 99%